OPTIMALISASI PRE EDUCATION YANG EXCELLENT PADA IBU NIFAS DALAM UAPAYA PROMOTIF DAN PREVENTIF STUNTING MELALUI PEMBERIAN ASI EKSKLUSIF DI DESA BANGUN REJO KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA TAHUN 2025 - Br.Manjorang, Novita Andriani; Erin Padilla Siregar; Sri Rezeki; Ade Rachmatb Yudianto; Plora Novita Sinaga (Bengkulu Institute, 2025)
In Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province, this community service project is to raise postpartum mothers' awareness of stunting prevention and promotion measures through exclusive breastfeeding by 2025. Breastfeeding exclusively for the first six months of life can help avoid stunting, a chronic nutritional issue that affects children's physical and cognitive development. The phases of planning, carrying out, assessing, and reporting are all included in the implementation approach. In addition to giving postpartum moms educational media, educational activities are offered in the form of counseling, interactive conversations, and simulations of proper nursing procedures. Pre- and post-tests were used for evaluation in order to gauge participants' knowledge growth. According to the findings, postpartum moms now have a better awareness of the value of exclusive breastfeeding, appropriate nursing practices, and how they relate to preventing stunting. By enabling postpartum moms to nurse exclusively, this activity is anticipated to help lower stunting rates